STUDI LITERATUR PEMANFAATAN PENGGUNAAN HASTAG SEBAGAI MEDIA PROMOSI PADA AKUN INSTAGRAM B&Y STUDIO - Abiyoga Ari Nugroho; Dena Assifa Arfah (Jurnal Teknologi Informasi dan Masyarakat, 2025)
The development of digital technology has driven a paradigm shift in marketing strategies, where social media serves as a primary channel for reaching consumers broadly and in real time. Instagram, as one of the dominant social media platforms, provides business analytics features that enable entrepreneurs to access comprehensive user behavior data. This study aims to analyze the utilization of hashtags as a strategic instrument in optimizing product marketing through Instagram. Using a descriptive-qualitative approach, this research explores how user interaction data can be processed into information that supports marketing decision-making. The findings indicate that an appropriate hashtag strategy can enhance content visibility, expand audience reach, and strengthen consumer engagement with the promoted products.